Formalization of Marriage Registration from the Perspective of Maqāṣid al-Sharī‘ah: A Comparative Study of Classical Islamic Jurisprudence and Family Law Regulations in Indonesia - Muhammad Syarif Dibaj; Muhammad Sauqi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The tension between the validity of theological marriage (classical fiqh) and its formal legality (state law) remains a crucial discourse in Indonesia, particularly in religious regions. Many people perceive marriage registration merely as an administrative burden with no implication for religious validity, leading to the prevalence of unregistered marriages. This normative legal research employs a statute approach and a conceptual approach. Data were gathered through a literature review of authoritative fiqh texts, Indonesian family law regulations, and the theory of Maqāṣid al-Syarī‘ah. The study reveals that the absence of discussions of marriage registration in classical fiqh was due to the historical communal socio-political context, which differs from modern state structures. Through the lens of Maqāṣid al-Syarī‘ah, the formalisation of marriage registration has risen from a ḥājiyyāt (secondary need) to a ḍarūriyyāt (primary necessity). This is because registration serves as the sole instrument in protecting wives’ civil rights (ḥifẓ al-māl) and ensuring children’s legal identity and lineage (ḥifẓ al-nasl) before positive law. This research concludes that marriage formalisation is a manifestation of public interest (maṣlaḥah mu’tabarah) that must be fulfilled to uphold substantive justice within Muslim family institutions in Indonesia.